Conjugated polymers for functional applications: lifetime and performance of polymeric organic semiconductors in organic field‐effect transistors. Issue 4 (4th May 2020) - Kimpel, Joost; Michinobu, Tsuyoshi
Abstract : Developments in the performance of organic field‐effect transistors have produced devices with similar, and in some cases even better, charge transport properties compared to amorphous silicon. For devices to be viable in more appliances and industry, their lifetime must be improved. However, advances in lifetime are lagging compared to other properties, such as charge carrier mobilities. The lack of a standardized methodology to evaluate the lifetime adds complications, as this property can mostly be compared qualitatively rather than quantitatively. Still, extension of lifetime has been realized through intelligent design of device architecture or alterations that benefit the stability of a device's active organic semiconducting polymer. More unique methods to improve the stability of organic field‐effect transistors, such as blending the semiconducting layer with other polymers or imposing micro‐/nanostructures in the device, have yielded positive results. © 2020 Society of Chemical Industry Abstract : The developments of the lifetime of organic field‐effect transistors containing polymeric organic semiconductors are reviewed. Changing the architecture, polymer structure alterations and other methods to improve lifetime are discussed.